QUALITY ANALYSIS OF THE ELECTRONIC GOVERNMENT PROCUREMENT ORDER SYSTEM USING WEBQUAL AND EUCS METHODS - Anshar Maulidi, Muhammad; Wahyuni, Evi Dwi; Wiyono, Briansyah Setio (Jurnal Techno Nusa Mandiri, 2024)
Within district of Hulu Sungai Selatan there is a website for the community to offer goods or services, namely SIOPEN, SIOPEN functions as a forum for the HSS community and umkm to offer their goods or services to the local government. The goal of this research is to evaluate SIOPEN's quality using the Webqual approach and users' degree of satisfaction using the EUCS approach. The Webqual approach, which has three dimensions information quality, usability, and interaction service was employed in this research together with the EUCS approach. The EUCS approach has some variables in partikular ease of use, accuracy, format, content, and timeliness. The approach of gathering information data through respondents via sending out online questionnaires to SIOPEN users and determining the sample using the formula from Slovin obtained 88 users then obtained by Webqual Index and Average Satisfaction. The results of research measuring the three dimensions of Webqual show that are in very good interpretation, The information quality dimension obtained 0.8392, the usability dimension obtained 0.8292, then the service interaction dimension obtained 0.8284. The findings from assessing the level of the satisfied user three variables of EUCS in particular content at a score of 4.27, ease of use at a score of 4.21, and timeliness at a score of 4.28 are at very satisfied level, then the other two variables are accuracy at a score of 4.15 and format at a score of 4.11 at a satisfied level.